A high performance grid connected PV system based on HERIC transformerless inverter - Essam Hendawi (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
This paper presents an effective single phase grid connected photovoltaic PV system based on High Efficiency and Reliable Inverter Concept HERIC transformerless inverter. Dc-dc boost converter controlled by incremental conductance IC maximum power point tracker MPPT is employed to achieve the maximum extraction power of the PV panels. Proportional integral PI controller controls the output voltage of the boost converter to meet the utility grid requirements. LCL filter is utilized to keep the inverter voltage very close to sinusoidal shape. Employing the HERIC transformerless inverter reduces significantly the ground leakage current beyond safe limits. Semiconductors losses are studied to investigate the efficiency of the proposed system at different insolation levels. Simulation results verify the high performance of the proposed system when considering leakage current and system efficiency.